2021
DOI: 10.1016/j.breast.2021.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Development of a novel nomogram-based online tool to predict axillary status after neoadjuvant chemotherapy in cN+ breast cancer: A multicentre study on 1,950 patients

Abstract: Background: Type of axillary surgery in breast cancer (BC) patients who convert from cN þ to ycN0 after neoadjuvant chemotherapy (NAC) is still debated. The aim of the present study was to develop and validate a preoperative predictive nomogram to select those patients with a low risk of residual axillary disease after NAC, in whom axillary surgery could be minimized. Patients and methods: 1950 clinically node-positive BC patients from 11 Breast Units, treated by NAC and subsequent surgery, were included from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 42 publications
0
6
1
Order By: Relevance
“…Both the distribution of intravascular contrast agents and the early enhancement mode could sensitively reflect the microvascular density and specific distribution of the body [ 11 ]. It was speculated that the main mechanism was as follows: breast cancer primary tumors of hemodynamic changes would affect axillary lymph node metastasis.…”
Section: Related Workmentioning
confidence: 99%
“…Both the distribution of intravascular contrast agents and the early enhancement mode could sensitively reflect the microvascular density and specific distribution of the body [ 11 ]. It was speculated that the main mechanism was as follows: breast cancer primary tumors of hemodynamic changes would affect axillary lymph node metastasis.…”
Section: Related Workmentioning
confidence: 99%
“…Several studies have confirmed the high correlation between breast pCR and axillary pCR. pCR in the axilla can be indirectly predicted by predicting breast pCR [ [14] , [15] , [20] ]. Especially for patients with high load such as cN2, it is very important to be able to assess the pathological response of the breast before surgery after NAT.…”
Section: Discussionmentioning
confidence: 99%
“…Although few cN2 patients were enrolled in the Z1071 study, sentinel lymph node biopsy was still feasible in this subset of patients with high axillary burden according to the results [ 13 ]. Studies have demonstrated a high correlation between axillary pCR and breast pCR in patients with cN + following NAT[ [14] , [15] ]. It is therefore hypothesized that patients with both TN and HER2-positive subtypes of cN2 who achieve pCR in their breast following NAT may be suitable candidates for undergoing only SLNB and avoiding axillary dissection.…”
mentioning
confidence: 99%
“…A recent international EUBREAST survey among 349 international breast units demonstrated that standard ALND or target ALND are still the preferred approach in these patients 14 . In 2021, our group developed and validated a post-NAC predictive nomogram to select cN + BC patients with a low risk of residual axillary disease after NAC in whom axillary surgery could be minimized 15 . To date, there are no validated tools to identify, before NAC, patients who are most likely to undergo node conversion.…”
Section: Trial Registrationmentioning
confidence: 99%